Evaluation by electrical bioimpedance method of selected morphological parameters of the body of women aged 19 to 26 not engaging in physical activity - Beata Całyniuk; Agata Malczyk (Śląski Uniwersytet Medyczny w Katowicach, 2022)
Introduction Inadequate nutrition and a lack of physical activity contribute to the development of many diseases, which may not be clinically manifested at first, therefore the regular monitoring of health is essential for its preservation. The basic test used in current practices is body composition analysis. This analysis makes it possible to assess the nutritional status of individuals as well as selected populations. It is widely available, simple to perform, non-invasive and therefore safe. The aim of the study was to assess the body composition of women aged 19 to 26 who are not physically active. Material and methods The study involved 548 women aged 19-26. Body composition was assessed using an electrical bioimpedance analyzer. The study provided information on the body fat mass, muscle mass, bone mineral mass, total body water, including intra-cellular body water and extra-cellular body water and the proportion of extra-cellular body water to total body water, as well as body mass index (BMI), the visceral tissue index, metabolic age and basal metabolic rate. Results Over 75% of the surveyed women aged 19-26 had normal body weight, and almost 90% had normal total body water. However, the ratio of extra-cellular body water to total body water was increased in 86.7% of the women surveyed. The ratio of extra-cellular body water to total body water increased statistically with age. Almost 45% of respondents were characterized by too high (at elevated and high level) body fat mass. The metabolic age in every third examined woman was higher than the record age. Conclusions The better nutritional status assessed on the basis of BMI and body composition analysis was characteristic for the women aged 21 comparing to the other examined women.